RELATIONSHIP BETWEEN PERSONALITY AND SELF-EFFICACY (International Journal of Food and Nutritional Sciences, 2022)
Research Background: According to, Baron, (1993), Personality is usually defined as an individual‘s unique and relatively stable patterns of behavior, thoughts, and emotions Albert Bandura (2008) captured the power of positive thinking in his research and theorizing about self-efficacy. Personality and self-efficacy both concepts are connected to each other. That is why in this study, the investigator finds out the relationship between personality and self-efficacy. Objectives: The study objective was, to find out the relationship between personality and self-efficacy of adults as well as impact of gender difference on self-efficacy of individuals. Procedure: For the study, two hundred adults were chooses from introvert personalities and same way two hundred adults were chooses from extrovert personalities. The purposive sampling technique had been used for the selection of the samples. The sample age range was between 35 and 60 years of age. This study introversion and extraversion inventory developed by Dr. P. F. Aziz and Dr. Rekha Gupta and self-efficacy scale developed by Dr. A. K. Singh and Dr. Shruti Narain have been used. Conclusions: It is concluded that, the extroverted adults have found in high levels of self-efficacy than introverted adults. The male and female adults have found equal on their self-efficacy. Other hand side, there is no significant difference found in the level of self-efficacy among the introvert male and female adults as well as the extrovert male and female adults. Application: The present study will definitely help us to understand the relationship between the type of personality and level of self-efficacy. The study will help us to understand the impact of the type of gender on the level of self-efficacy.